2006
DOI: 10.1097/00149831-200606000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and clinical significance of exercise-induced increases in cardiac troponins and N-terminal pro brain natriuretic peptide in endurance athletes

Abstract: Due to the missing reproducibilty and evidence of myocardial damage, exercise-induced increases in cardiac troponins may represent a physiologic reaction under special conditions and seem to be without pathological significance in healthy athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 34 publications
4
27
0
2
Order By: Relevance
“…It is important to mention that a significant increase in BNP or proBNP after exposure to HBO (68) and simulated diving (69), and also even after studying the effects of immersion (70) and exposure to cold (71) was not observed. Considering these data and the fact that numerous studies have shown an increase of BNP levels after exercise (7276), it is evident that physical activity plays an important role in BNP increase after diving.…”
Section: Cardiovascular Response To Scuba Divingmentioning
confidence: 85%
“…It is important to mention that a significant increase in BNP or proBNP after exposure to HBO (68) and simulated diving (69), and also even after studying the effects of immersion (70) and exposure to cold (71) was not observed. Considering these data and the fact that numerous studies have shown an increase of BNP levels after exercise (7276), it is evident that physical activity plays an important role in BNP increase after diving.…”
Section: Cardiovascular Response To Scuba Divingmentioning
confidence: 85%
“…Alternatively, the leakage could be related to other factors, as has been observed in endurance athletes with elevated troponin levels but no evidence of myocardial necrosis on magnetic resonance imaging (MRI). 13 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is tempting to suggest that the appearance of cTnI after physical exercise does not reflect a clinically threatening (irreversible) myocardial injury, but rather may reflect a reversible increase in cellular membrane permeability and rapid troponin release from the cytosolic pool post-exercise (Lippi and Plebani 2009). Some authors have suggested that exercise-induced cTn release reflects the activation of cellular cascades that result in cardiac hypertrophy (Scharhag et al 2006). Changes in cellular membrane permeability, subsequent to an increased rate and force of cardiac contraction during endurance exercise, may provide a mechanism by which cytosolic troponin is released into the circulation after exercise.…”
Section: Discussionmentioning
confidence: 99%